Reconstructing William Lane Craig’s Explanation of Absolute Time Based on Mulla Sadra’s Philosophy - Kavyani, Mohammad Sadegh (Sophia, 2025)
After the advent of the theory of special relativity, the existence of absolute time in nature was rejected within the society of physics. In recent decades, William Lane Craig has endeavoured to offer an interpretation of the empirical evidence that support the theory of relativity while maintaining the concept of absolute time. His interpretation, however, is based upon supernatural presuppositions due to which it cannot be accepted as a scientific argument. After explaining Craig’s view, we attempt to reconstruct his explanation for absolute time using the concept of general substantial motion of nature, well-known in Mulla Sadra’s philosophy as the most important approach in Islamic philosophy; thereby, proving general time for the natural world. Although Craig considers some evidence from modern physics in his reasoning for absolute time, here, after pointing to some evidence, it is discussed that the approach used here better bridges the gap that exists between the metaphysics and the physics of the argument.